Obraz Ameryki w opublikowanej korespondencji Czesława Miłosza z lat 1945-1950 - Kołodziejczyk, Ewa (Tematy i Konteksty, 2011)
The article reconstructs the portrait of the United States of America depicted in the published correspondence of Czesław Miłosz from the years 1945-1950. The article discusses the circumstances that caused the poet to undertake his job as a diplomat abroad and motivations of his decision. The article analyses also a variety of opinions discussed by environments of both Polish and émigré writers related to that decision. Finally, it marks the changes that occurred in Miłosz’s attitude towards the autobiography he wrote and duties he performed after the war. The article compares the poet’s juvenile visions of the United States with the reality he faced after his arrival to the New World. The article discusses also the culture shock and slow process of acclimatization the poet experienced and treated, on the intellectual level, as a process of rejecting the materialistic perception of American culture in favor of the perception of its symbolic aspects. The article discusses the subsequent stages and elements of the self-education process undertaken by Miłosz through not only extensive reading but also his translations from English-language literature, literary and sociopolitical journalism discussing American issues but published in Polish magazines and finally – his organizational work for publishing industry and academic institutions. The conclusion of the article presents the poet as a mediator between the Old and the New World he became just before his return to Europe.